Evaluation of school sports insurance with medical assistance (One Health & Risk Management, 2023)
Introduction. In the Republic of Moldova, the majority of athletes are young people, including children. The health status of the athletes trained in the schools with the respective profile, their physical and intellectual development, the implementation of a healthy lifestyle largely depends on the provision of the nominated educational institutions with the necessary spaces for activities, equipment as well as, competent medical personnel and professional coaches c.The aim of the research. To assess the provision of sports institutions in the Republic of Moldova with medical personnel (doctors, nurses, physiotherapists) and conditions for medical assistance.Material and methods. The study was carried out based on a questionnaire sent to the e-mail addresses of sports schools in the Republic of Moldova. The questionnaire included questions addressed to the managers of these institutions, regarding the availability of medical personnel, the ratio of medical staff to athletes, the adequacy of space, the number of coaches, the number of athletes in each institution, and the range of sports activities offered.Results.There are currently 37.900 individuals registered in schools with a sports profile in the Republic of Moldova, including 19.1 thousand beginner athletes, 17.7 thousand advanced athletes, 0.9 thousand people at the sports mastery level, 0.2 thousand at the higher master of sports level, 128 candidates for masters of sports, 59 masters of sports and 44 international masters of sports. Most of the sports schools in the Republic of Moldova are provided with sufficient medical and teaching staff, they have activity spaces, but not enough for a professional sports activity to achieve the expected results and ensure a healthy training environment. Sports schools in the country are provided with medical personnel in accordance with the stable staffing scheme. However, many of the medical staff in sports schools also work in other medical institutions or are retired individuals without special training in the field of sports medicine. Sports schools have space for providing medical assistance, but they are insufficiently equipped with medical equipment and materials. For the training of the medical personnel working in the nominated institutions, it is necessary to create a continuous training of competence in the field of sports medicine within the Nicolae Testemițanu State University of Medicine and Pharmacy in the Republic of Moldova. Based on the requests received from the administration of the sports schools, the "Atletmed" National Centre for Sports Medicine has offered itself as a clinical base for the training of medical staff in the field of sports medicine and requested the organization of a competency course in sports medicine for doctors from other specialties.Conclusions. Sports schools in the Republic of Moldova are generally provided with medical staff and necessary facilities, many specialists would benefit from competency courses in the field of sports medicine.